Operative versus Nonoperative Treatment in Patients with Advanced Non-Small-Cell Lung Cancer: Recommended for Surgery - Hui Wang; Di Yang; Yan Lv; Jing Lin; Haibin Wang (Canadian Respiratory Journal)
Background. There is currently limited evidence for a correlation between the recommended operation and overall survival (OS) in patients with advanced non-small-cell lung cancer (NSCLC). Methods. NSCLC patients with stages III and IV, recommended for operation, were identified in the US National Cancer Institute Surveillance, Epidemiology, and End Results database (SEER).We used propensity score matching (PSM) and multivariable Cox proportional hazards regression to ensure the robustness of our findings. The cumulative rates of death were compared between patients with and without recommended operations using the Kaplan−Meier curves. Results. Operation was recommended for 3331 patients but was not performed in 912 (27.4%) patients (then on-operative group). After PSM, 553 pairs matched. Compared to the nonoperative group, the hazard ratios (HRs) in the operative group were 0.46 (95% CI 0.23–0.95 and p=0.037) in stage IIIA and 0.54 (95% CI 0.42–0.68 and p<0.001) in stage IVA. However, in stages IIIB, IIIC, and IVB, the recommended operative group was not associated with better OS. The OS was not different in stage IIIA-N2, stage IVA-N1, and stage IVA-N3 patients between groups (p=0.28, p=0.14, and p=0.79, respectively). Moreover, the recommended operative group had better OS than the nonoperative group in stage IIIA-N0 (p=0.00085), stage IIIA-N1 (p=0.009), stage IVA-N0 (p<0.001), and stage IVA-N2 (p=0.034). Conclusion. Compared to the nonoperative group, recommended operation improved survival in NSCLC patients with stage IIIA-N0, stage IIIA-N1, stage IVA-N0, and stage IVA-N2. However, in stages IIIA-N2, IIIB, IIIC, IVA-N1, IVA-N3, and IVB, recommended operation did not lead to significantly improved survival time.